The impact of financial flexibility on companies value (Study applied for the banking sector listed on the Iraq Stock Exchange for the period from (2010-2019)) - Luma Mohammed Mansour; Shatha Abdul-Hussein Jabr; Mohammed Ali Musa (Journal of Madenat Alelem University College, 2022)
Abstract   The research aims to identify the extent of the impact of financial flexibility on the value of banks listed on the Iraq Stock Exchange, as well as analyzing the indicators of the research variables, financial flexibility (leverage ratios, liquidity ratios) as an independent variable, and the value of companies (market value shares) as a dependent variable. The research community commercial banks listed on the Iraq Stock Exchange, has been chosen as the (10) ten commercial banks as a sample for the study research period was (10) ten years (2010-2019). Using the financial statements published on the Iraqi Stock Exchange website. It sought to test a main hypothesis. It sought to test a research hypotheses, The effect relationship between the study variables that was used to test the effect relationships between the study variables, and relations of influence between the variables of the study, in order to answer the questions related to the problem of the study and to reach the goals set.For processing the data, it was used many financial equations. The results were extracted using the Excel software.    The study reached a number of conclusions, including that the ability of banks to face external shocks and achieve acceptable levels, by maintaining liquidity and following a moderate financial raising policy that came as a result of their reliance on a flexible financial policy that made them better than other banks.